Hydrothermal structure of a polythermal glacier in Spitsbergen by measurements and numerical modeling - A. V. Sosnovsky; Yu. Ya. Macheret; A. F. Glazovsky; I. I. Lavrentiev (Лëд и снег)
Thickness of the upper cold ice layer in the ablation area of the polythermal glacier Grønfjordbreen (Spitsbergen) was estimated by means of numerical modeling. The results were compared with data of radio-echo sounding of the same glacier obtained in 1979 and 2012. Numerical experiments with changing water content in the lower layer of temperate ice and surface snow cover thickness made possible to compare calculated and modeled cold ice thicknesses and to estimate their changes for 33‑year period caused by regional climate change. According to data of radio-echo sounding, thickness of the cold ice layer decreased, on average, by 34 m. Numerical modeling shown similar results: the cold ice layer became thinner by 31 m and 39 m at altitudes 100–300 a.s.l. under the snow cover thickness of 1 m and 2 m. We explain this by rising of annual mean air temperature by 0,6 °С as compared to data of the nearest meteorological station Barentsburg in the same period. We believe that changes in cold ice layer thickness in polythermal glaciers can be used for estimation of changes in such regional climatic parameter as mean air temperature at different altitudes of the glacier surface in the ablation area.